2004
DOI: 10.1097/00005537-200410000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of the Nose in Human Embryos: A Stereomicroscopic and Histologic Analysis

Abstract: The development of the nose is most active from Carnegie stage 13 to 19, which corresponds to the end of the fourth embryonic week to the end of the seventh week. Thus, this period is considered to be the most important period in human nasal embryonic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…The medial nasal prominence is fused with the maxillary prominence anteriorly and the lateral nasal prominence posteriorly, as seen with histological sections (Pruzansky, 1961; Tamarin and Boyde, 1977; Diewert and Wang, 1992; Rudé et al, 1994; Kim et al, 2004) and in scanning electron micrographs (Sperber, 2002; Jiang et al, 2006). …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The medial nasal prominence is fused with the maxillary prominence anteriorly and the lateral nasal prominence posteriorly, as seen with histological sections (Pruzansky, 1961; Tamarin and Boyde, 1977; Diewert and Wang, 1992; Rudé et al, 1994; Kim et al, 2004) and in scanning electron micrographs (Sperber, 2002; Jiang et al, 2006). …”
Section: Introductionmentioning
confidence: 86%
“…Indeed there has been a general lack of consensus on which prominences initiate fusion in amniotes. A series of studies in chicken (Sun et al, 2000; Ashique et al, 2002; Cox, 2004) and human (Pruzansky, 1961; Diewert and Wang, 1992; Rudé et al, 1994; Sperber, 2002; Kim et al, 2004) concluded that the maxillary and medial nasal prominences are the first to contact each other. On the other hand, most studies carried out on mouse embryos found that the medial nasal and lateral nasal prominences are the first to fuse at E10.5-E11.0 (Trasler, 1968; Gaare and Langman, 1980; Wang et al, 1995; Gong and Guo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They then become more concave forming the nasal pit. The mesenchyme proliferates around the placode establishing the medial and lateral nasal prominences while the nasal pit becomes deeper, forming the nasal cavities (Kim et al 2004). The paranasal sinuses develop during late fetal life and in infancy as diverticula of the lateral nasal walls.…”
Section: Origin and Organization Of The Respiratory Tractmentioning
confidence: 99%
“…The stage between the end of the 4th week to the 7th week is the most active, important period in the human nose development [O'Rahilly, 1967;Kim et al, 2004]. A failure of the developmental process may result in arhinia, for example, failure of growth or overgrowth of the medial and lateral nasal process sequentially leads to premature fusion of the medial nasal processes [Albernaz et al, 1996].…”
Section: Resultsmentioning
confidence: 99%